SIDE EFFECTS PROFILE OF ANTIPLATELET MEDICATION IN PATIENTS WITH CORONARY HEART DISEASE AT BHAYANGKARA HOSPITAL BALI-INDONESIA - Astrijayanti, Anak Agung Indah; Jaya, Made Krisna Adi; Sutema, Ida Ayu Manik Partha; Evayanti, Ni Putu Wulanda; Purnamisari, Ni Ketut Tria (Journal Pharmaceutical Science and Application; Vol 2 No 2 (2020): Journal Pharmaceutical Science and Application, 2020)
Introduction: Coronary heart disease (CHD) is a disorder of heart function due to a lack of blood in the heart muscle due to narrowing of the coronary arteries. Antiplatelet in patients with CHD is a therapy that must be obtained by patients throughout their lives to prevent recurrent attacks and deaths from CHD. In the Province of Bali, especially in Denpasar, there is a lack of information about the type of side effects that occur on antiplatelet medication, so it is necessary to do a related study. Objective: The aim of this study is to identify the type of side effects that occur on antiplatelet medication in patients with CHD. Methods: A cross-sectional study involving 97 patients was done by observed the CHD patients treated with antiplatelet medication. Side effects were evaluate using Naranjo Algorithm. Patients were divided into three groups, including a low dose aspirin user group, clopidogrel user group, and aspirin-clopidogrel combination user group. Results: Antiplatelet side effects that occur in patients include headache (2.06%), diarrhea (1.03%), cyanosis (1.03%), gastrointestinal bleeding (8.25%), heartburn (11.34%), and nausea (6.19%). These side effects only occurred in 31.96% of the total subjects. The incidence of aspirin side effects was significantly greater than clopidogrel as well as aspirin-clopidogrel in combination (p <0.05). Conclusion: Patients with CHD who use antiplatelet agents in the long term to be more aware of the potential side effects that will occur, especially heartburn in chronic low-dose aspirin users. Keywords: Coronary Heart Disease, Side Effects, Antiplatelet, Aspirin, Clopidogrel